2011
DOI: 10.1007/s00270-011-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: An Independent Risk Factor for Insufficient Hemostasis Using the AngioSeal Vascular Closure Device After Antegrade Puncture

Abstract: Obesity seems to be an independent risk factor for insufficient sealing using the AngioSeal vascular closure device after antegrade puncture of the CFA. In 8% of our patients, hemostasis could not be achieved due to kink of the flexible sheath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…On baseline analyses, patients who were treated with a CD had a higher proportion of obesity, which has previously been reported to independently predict access site complications in patients undergoing antegrade PVI, even when a CD was used. 12 The burden of overall atherosclerotic disease was lower in the CD group compared with the no CD group, as indicated by a lower proportion of patients with a history of CAD, CABG, PCI, major amputation, and previous inflow or infrainguinal stent, angioplasty, or bypass. Patients receiving an intervention owing to occlusive disease were also less likely to be treated with a CD.…”
Section: Discussionmentioning
confidence: 87%
“…On baseline analyses, patients who were treated with a CD had a higher proportion of obesity, which has previously been reported to independently predict access site complications in patients undergoing antegrade PVI, even when a CD was used. 12 The burden of overall atherosclerotic disease was lower in the CD group compared with the no CD group, as indicated by a lower proportion of patients with a history of CAD, CABG, PCI, major amputation, and previous inflow or infrainguinal stent, angioplasty, or bypass. Patients receiving an intervention owing to occlusive disease were also less likely to be treated with a CD.…”
Section: Discussionmentioning
confidence: 87%
“…So far, only obesity has been reported as an independent risk factor for deployment failure in antegrade punctures. 22 In contrast though, other papers examining this issue in the context of percutaneous EVAR have suggested that BMI is not relevant to VCD deployment success rates, though of course punctures in such cases are by default retrograde. 23 It is certainly our experience that traversing through a fatty/deep groin in an antegrade fashion can create a right angle kinking the Angio-Seal sheath, which may contribute to deployment difficulty and failure.…”
Section: Discussionmentioning
confidence: 99%
“…The StarClose system, a clip based device, has a malfunction rate around 1.1%. AngioSeal, a well-established collagen plug induced vascular closure device, has been found to have malfunction rates up to 10% [13,14]. The majority of the device malfunctions occurred at the beginning of the Secure Device activation, so the device was able to be changed and did not influence the study procedure.…”
Section: Discussionmentioning
confidence: 99%